Aspectos bioecológicos e pesqueiros de três espécies de camarões do gênero Penaeus nas costas do Estado do Rio de Janeiro e experimentos de cultivo - Silva, Olintho da (1977)
Some aspects of the Biology, or in particular of the Ecology, the Fishing, and experiments of culture of the three species of shrimps of the most important commercial goals for the Fishing in the State of Rio de Janeiro, are considered as follows: a) Penaeus brasiliensis (pink spotted shrimp); b) Penaeus paulensis (brown shrimp); and e) Penaeus schmitti (white shrimp). Some aspects of taxonomy of the most importance were discussed. Research-workers of our country as well as other countries, have been studying the shrimps of the genus Penaeus Fabricius, 1798 in the Brazilian offshore. The present dissertation is part of observations for the littoral of the State of Rio de Janeiro, and also through field and/or laboratory works which were developed, directly, on board research fishing ships and the commercial fleet, as well as on land.